Skin Biomarkers for Cystic Fibrosis: A Potential Non-Invasive Approach for Patient Screening - Esteves, Cibele Zanardi; de Aguiar Dias, Letícia; de Oliveira Lima, Estela; de Oliveira, Diogo Noin; Rodrigues Melo, Carlos Fernando Odir; Delafiori, Jeany; Souza Gomez, Carla Cristina; Ribeiro, José Dirceu; Ribeiro, Antônio Fernando; Levy, Carlos Emílio; Catharino, Rodrigo Ramos (Frontiers in Pediatrics, 2018)
Background: Cystic fibrosis is a disabling genetic disease with an increased prevalence in European heritage populations. Currently, the most used technique for collection of cystic fibrosis samples and diagnosis is provided through uncomfortable tests, with uncertain results, mostly based on chloride concentration in sweat. Since cystic fibrosis mutation induces many metabolic changes in patients, exploring these alterations might be an alternative to visualize potential biomarkers that could be used as interesting tools for further diagnostic upgrade, prioritizing simplicity, low cost and quickness. Methods: This contribution describes an accurate strategy to provide potential biomarkers related to cystic fibrosis, which may be understood as a potential tool for new diagnostic approaches and/or for monitoring disease evolution. Therefore, the present proposal consists of using skin imprints on silica plates as a way of sample collection, followed by direct-infusion high-resolution mass spectrometry and multivariate data analysis, intending to identify metabolic changes in skin composition of cystic fibrosis patients. Results: Metabolomics analysis allowed identifying chemical markers that can be traced back to cystic fibrosis in patients’ skin imprints, differently from control subjects. Seven chemical markers from several molecular classes were elected, represented by bile acids, a glutaric acid derivative, thyrotropin releasing hormone, an inflammatory mediator, a phosphatidic acid, and diacylglycerol isomers, all reflecting metabolic disturbances that occur due to of cystic fibrosis. Conclusion: The comfortable method of sample collection combined with the identified set of biomarkers represent potential tools that open the range of possibilities to manage cystic fibrosis and follow the disease evolution. This exploratory approach points to new perspectives about the development of diagnostic assay using biomarkers and the management cystic fibrosis.